Carotenoid and Moisture Stability of Red Fruit (Pandanus conoideus) Oil Powder during Storage - Dewi, Desak Putu Ariska Pradnya; William, William; Tanardi, Samantha; Katherine, Katherine; Mas, Muhammad Abdurrahman; Surjawan, Iwan (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The aim of this study was to evaluate the carotenoid and moisture stability of spray-dried and freeze-dried red fruit oil with different wall materials during storage. Red fruit emulsion was prepared by mixing sodium caseinate, maltodextrin and whey protein isolate in different ratios (1:0 (MW1), 3:1 (MW2), 1:3 (MW3) and 0:1 (MW4)), water, and red fruit oil followed by spray or freeze drying. The result showed that the carotenoid content of all samples was stable, but the moisture content changed during storage. Freeze-dried samples showed higher carotenoid and moisture content compared to spray-dried samples throughout the storage.